INDONESIA'S EFFORT IN SEAWEED RE-EXPORTATION TO THE UNITED STATES - Hendra Kurniawan; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research explains about the efforts of Indonesia in re-exporting seaweed to the United States. Indonesia has a vast sea area with waters that have abundant marine resources, one of which is seaweed, the potential for seaweed in Indonesia has promising economic sales, abundant seaweed production, and good quality, making Indonesia a seaweed exporter to several countries. one of them is the United States, The United States wants to delist Indonesian seaweed which results in huge losses to Indonesian seaweed exports.The perspective used in this research is liberalism based on the assumption that humans are essentially creatures who do not like conflict, are willing to cooperate, and are rational. The theory used is the theory of international cooperation. The level of analysis in this study is the nation state. The focus of this research is to examine how the behavior of the country's foreign policy in terms of the characteristics of the country. The data for this research were taken from books, journal articles, documents (government output and NOSB) and websites.Indonesia must find a solution so that its seaweed can still enter the United States in one way, namely Indonesia takes international trade negotiations with the United States and applies the standards that have been applied by the United States National Organic Standardization Agency.Keywords: United States, Indonesia, ASIC, Delisting, Efforts, Foreign Policy.